1994
DOI: 10.1111/j.1476-5381.1994.tb13164.x
|View full text |Cite
|
Sign up to set email alerts
|

Poly‐l‐arginine‐mediated release of acetylcholine from parasympathetic nerves in rat and guinea‐pig airways

Abstract: 1 The synthetic cationic polypeptide, poly-L-arginine (0.03-1 mg ml-') induced concentrationdependent contraction of guinea-pig and rat isolated trachea. In guinea-pig isolated trachea, this response was attenuated in the presence of the muscarinic cholinoceptor antagonist, atropine (0.1 gM) and augmented by the acetylcholinesterase inhibitor, ecothiophate (0.1 M). The neuronal sodium channel blocker, tetrodotoxin (3 .M) failed to alter the contractile response to poly-L-arginine and acetylcholine. 2 The contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We [ 18 ] have previously shown that MBP directly elicits airway myocyte calcium mobilization. Others have shown that an indirect effect of MBP may be through an effect on epithelial-derived mediator release [ 32 34 ], increased epithelial permeability [ 35 ], cytotoxicity [ 36 ], or by inhibiting muscarinic M 2 receptors [ 16 ]. These conflicting results may be due to the manner in which purified MBP is applied to tissues and cells in culture.…”
Section: Discussionmentioning
confidence: 99%
“…We [ 18 ] have previously shown that MBP directly elicits airway myocyte calcium mobilization. Others have shown that an indirect effect of MBP may be through an effect on epithelial-derived mediator release [ 32 34 ], increased epithelial permeability [ 35 ], cytotoxicity [ 36 ], or by inhibiting muscarinic M 2 receptors [ 16 ]. These conflicting results may be due to the manner in which purified MBP is applied to tissues and cells in culture.…”
Section: Discussionmentioning
confidence: 99%
“…We could not use higher concentrations of poly-L-arginine due to the ability of this synthetic polypeptide to contract airway smooth muscle (Spina & Goldie, 1994a). Indeed, we have demonstrated that the poly-L-arginine-induced contraction of guinea-pig isolated trachea is mediated via the release of acetylcholine from parasympathetic nerves (Spina & Goldie, 1994b).…”
Section: Discussionmentioning
confidence: 99%
“…The role of eosinophils in asthma is a consequence of their abilities to secrete eosinophil granule proteins, including major basic protein (MBP), which is highly basic and cationically charged [9]. MBP released from activated eosinophils may generate AHR by either direct effects on airway myocytes or indirect effects [10] through the release of epithelial-derived mediators [1113], resulting in increased epithelial permeability [14], cytotoxicity [15], or the inhibition of muscarinic M2 receptors [16]. The effects of MBP can be mimicked by PLA, a synthetic cationic polypeptide.…”
Section: Introductionmentioning
confidence: 99%